Blueberry Muffin Baby: An Unusual Presentation of Infantile Neuroblastoma - Kumar, Mritunjay; Batra, Gaurav; Saun, Aditya; Singh, Ragini (Indian Journal of Medical and Paediatric Oncology, 2018)
Neuroblastoma is the most common solid tumor of infancy presenting clinically in a plethora of different and sometimes unpredictable ways with a wide range of symptoms. Young children can present with bluish skin metastases that may resemble bruising secondary to child abuse. Blueberry muffin baby had been reported to be a manifestation of either dermal erythropoiesis secondary to some congenital viral infections or neoplastic infiltrations. Among the neoplastic diseases, neuroblastoma has been the most common association with these subcutaneous skin metastases. Here, we report 2 months infant with neuroblastoma who presented with abdominal distension and multiple blueberry muffin nodules.
Keywords: Blueberry muffin; children; metastasis; neuroblastoma; skin